Patient Sleep Quality in Acute Inpatient Rehabilitation. Issue 12 (22nd February 2021) - Davis, Shane M.; Mekany, Majid; Kim, Jeff J.; Han, Jay J.
Abstract: Background: Sleep is an important component of neurorehabilitation. This study evaluates sleep quality in the acute inpatient rehabilitation setting and is the first to compare sleep quality in acute rehabilitation versus the acute care hospital and home settings. Objective: To assess patient sleep quality in the acute inpatient rehabilitation setting. Design: Cross‐sectional survey study. Setting: Acute inpatient rehabilitation unit. Patients: Seventy‐three patients admitted to the acute rehabilitation unit participated in the study. Interventions: A validated sleep questionnaire was provided on admission regarding sleep at home and in the acute care hospital. The questionnaire was repeated on discharge from the acute rehabilitation unit regarding sleep during their rehabilitation admission. Main Outcome Measures: Visual analog scale of sleep depth, falling asleep, number of awakenings, percentage of time awake, and quality of sleep were obtained through use of the Richards‐Campbell Sleep Questionnaire. These values were averaged to obtain "overall sleep perception." An additional question on environmental noise was added. Scores ranged from 0 for "worst sleep possible" to 100 for "best sleep possible." Results: Patients reported significantly better sleep in all domains and overall in the acute rehabilitation unit compared to the acute care hospital, with the exception of percentage of time awake. Patients also reported significantly better sleep depth but worse noise in the acute rehabilitation unit when compared to home. Similarly, patients reported significantly better sleep in all domains and overall at home in comparison to the acute care hospital with the exception of percentage of time awake. Conclusions: Patient in the acute rehabilitation unit experience sleep quality that matches their experience at home and exceeds that in the hospital.